Characterization Of Tics in Peruvian companies - Verastegui Huanca, Lucio Leo (2020)
This work describes Information and Communication Technologies (ICT) in Peruvian companies according to the 2015 Enterprise Survey made by the National Statistical Institute (INEI). It has been chosen variables related to companies and ICTs to describe their use in the business management of companies in Peru. STATA software has been used to systematize and analyze the data with revealing results. This research will serve as the basis for other correlational and causal research.